Industrial Labour Force of Russia in 20-30s of XX Century in Russian Historiography - Oleg V. Shekatunov; Konstantin G. Malykhin (Научный диалог)
The article is devoted to the specifics of studying the industrial labour force of Russia in the 1920s - 1930s in Russian historiography. The various stages of study from the 1920s through the 1930s and up to the last years are concerned. The relevance of the study is due to several factors. These include contradictions in the assessments of Bolshevik modernization of the 1920s and 1930s; projected labour force shortages in modern Russia; as well as the existing labour force shortage in industry at the moment. This determines the relevance of studying the historical period, which was characterized by the most acute personnel problems in the country. The novelty of the study is due to the fact that in modern Russian historiography there is no holistic, integrated view of the problems of the labour force potential formation of Russian industry in the 1920s and 1930s. It is noted that there is no research aimed at analyzing the historiography of these problems. The main stages of the study of industrial labour force are highlighted. The analysis of scientific works correlated with each stage of the study of the topic is performed. The problems and methodology of each stage are considered. A review of a wide range of scientific papers both articles and thesis is presented.